Synthesis, characterization and investigation of electrochemical and spectroelectrochemical properties of peripherally tetra 4-phenylthiazole-2-thiol substituted metal-free, zinc(II), copper(II) and cobalt(II) phthalocyanines - KOCA, ATIF (ELSEVIER SCIENCE BV, 2017)
In this study novel peripherally tetra 4-phenylthiazole-2-thiol substituted metal-free phthalocyanine (4) and its zinc(II) (5), copper(II) (6) and cobalt(II) (7) derivatives were synthesized and characterized by a combination of various spectroscopic techniques such as FT-IR, H-1-NMR, UV-vis and MALDI-TOF mass. Electrochemical characterizations of metallo-phthalocyanine complexes were conducted by voltammetric and in situ spectroelectrochemical measurements. (CoPc)-Pc-II went [(CoPc-2)-Pc-II]/[(CoPc-2)-Pc-I](1-), [(CoPc-2)-Pc-I](1-)/ [(CoPc-3)-Pc-I](2-), [(CoPc-3)-Pc-I](2-)/[(CoPc-4)-Pc-I](3-) and [(CoPc-2)-Pc-I]/[(CoPc-2)-Pc-II](1+) reduction and oxidation processes respectively. Differently (ZnPc)-Pc-II only showed four ligand-based reductions and two ligand based oxidation processes. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Phenylthiazole; Electrochemistry; Spectroelectrochemistry; STRUCTURAL-CHARACTERIZATION; PHOTOCHEMICAL PROPERTIES; CU(II) PHTHALOCYANINES; THIAZOLE; METALLOPHTHALOCYANINES; BEARING; DERIVATIVES; COMPLEXES; ANTITUMOR; OXIDATION